2022
DOI: 10.3389/fnut.2022.886078
|View full text |Cite
|
Sign up to set email alerts
|

Natural Mineral Waters and Metabolic Syndrome: Insights From Obese Male and Female C57BL/6 Mice on Caloric Restriction

Abstract: Metabolic syndrome (MetS) represents one of the greatest challenges to public health given its serious consequences on cardiovascular diseases and type 2 diabetes. A carbohydrate-restricted, low-fat diet is the current therapy for MetS. Natural mineral waters (NMWs) are known to exert beneficial effects on human health. Our primary objective was to shed light on the potential therapeutic properties of NMWs in MetS. A total of 125 C57BL/6 male and female mice were included in the study. Of these, 10 were left u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Males were included to allow for comparisons to previous studies establishing dysregulation of SPMs 24 h following AgNP exposure. Additionally, male mice demonstrate a greater differential in terms of disease (weight gain and dyslipidemia) compared to females on the HFW diet making them the initial model to use to investigate disease and lipid signaling [30,79,80]. Subsets of mice were exposed to either 50 µl of water (control) or 50 µg of 20 nm AgNP via oropharyngeal aspiration (50 µL of stock AgNPs a concentration of 1 mg/mL in water).…”
Section: Agnp Characterizationmentioning
confidence: 99%
“…Males were included to allow for comparisons to previous studies establishing dysregulation of SPMs 24 h following AgNP exposure. Additionally, male mice demonstrate a greater differential in terms of disease (weight gain and dyslipidemia) compared to females on the HFW diet making them the initial model to use to investigate disease and lipid signaling [30,79,80]. Subsets of mice were exposed to either 50 µl of water (control) or 50 µg of 20 nm AgNP via oropharyngeal aspiration (50 µL of stock AgNPs a concentration of 1 mg/mL in water).…”
Section: Agnp Characterizationmentioning
confidence: 99%
“…Animal studies also proved that the consumption of low mineral water leads to a higher risk of cardiovascular disease [16] and impaired bone quality [18]. Meanwhile, the consumption of natural mineral water may contribute to controlling blood lipid and glucose levels [19], improving glycemic control [20], and maintaining bone health in young rats with metabolic acidosis [21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, more recently, other possible positive effects for human health determined as being caused by natural mineral waters have been evaluated. For example, a study was performed to evaluate the potential therapeutic properties of mineral water in metabolic syndrome and the results suggested that water minimally mineralized and those rich in specific macronutrients (bicarbonate, sulphate and magnesium), in combination with a low-calorie diet, may contribute to control glucose levels and blood lipid in subjects affected by metabolic syndrome [ 13 ]. Another study carried out to investigate the possible role of mineral water in intestinal inflammation verified that calcium and magnesium sulphate, sodium chloride, carbonic, and ferruginous water or bicarbonate one present positive effects on intestinal inflammation and the mucosa-associated microbiota [ 14 ].…”
Section: Introductionmentioning
confidence: 99%